Republic Of Latvia : Detailed Assessment Of Anti-Money Laundering And Combating The Financing Of Terrorism. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Detailed Assessment on Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for the Republic of Latvia. The assessment reveals that aspects of Latvia's financial services market expose it to a high risk of money laundering. There are welcome indications that money laundering risks have been reduced substantially owing to strong preventive measures being implemented by the authorities and financial institutions. The authorities and financial institutions are working to restore the international reputation of the Latvian financial sector.